2017
DOI: 10.1002/jca.21584
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell mobilization in patients with dialysis‐dependent multiple myeloma: Report of the Polish Myeloma Study Group

Abstract: The success rate in terms of obtaining sufficient number of CD34(+) cells/kg for an auto-HSCT (≥2 × 10 cells/kg body weight) during the first mobilization attempt was 92% (26/28 patients), and for 2 auto-HSCTs (≥4 × 10 cells/kg) - was 75% (21/28 patients). After the second mobilization attempt (undertaken in 8 patients), a sufficient number of CD34(+)/kg cells for an auto-HSCT was obtained for all patients and the number of CD34(+)/kg collected cells was sufficient for 2 auto-HSCT in 6 additional patients. Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Overall response rate (ORR) before auto‐PBSCT had 78% of patients. The single stem cell mobilisation procedure was successful in 20 patients, whilst 4 patients required a second mobilisation attempt due to an insufficient number of cells collected during the first yield, as previously reported …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Overall response rate (ORR) before auto‐PBSCT had 78% of patients. The single stem cell mobilisation procedure was successful in 20 patients, whilst 4 patients required a second mobilisation attempt due to an insufficient number of cells collected during the first yield, as previously reported …”
Section: Resultssupporting
confidence: 67%
“…The single stem cell mobilisation procedure was successful in 20 patients, whilst 4 patients required a second mobilisation attempt due to an insufficient number of cells collected during the first yield, as previously reported. 17 We found no statistically significant differences between DD and NRF patients at diagnosis regarding first line chemotherapy (P < .10), number of chemotherapy lines (P = 1.00) while in DD patients we observed significantly different distribution (P < .010) of the type of monoclonal protein (percentage of monoclonal protein lambda light chain was: 33% vs 5%, P < .001), higher creatinine concentration at diagnosis (8.3 vs 0.9 mg/dL, P < .001), higher albumin concentration (3.6 vs 3.3 g/dL; P < .002), higher frequencies of performance status (WHO) of 2 (38% vs 13%, P < .057) and different distribution of responses before auto-PBSCT (P < .031).…”
Section: Re Sultsmentioning
confidence: 99%
“…116 In patients with severe renal failure, stem cells can be successfully mobilised using single-agent G-CSF. 117 Plerixafor can be used at a reduced dose in patients with a glomerular filtration rate (GFR) 20-50 ml/min, but there are no data to support its use in those with a GFR <20 ml/min.…”
Section: Stem Cell Mobilisationmentioning
confidence: 99%
“…All the patients had performance status 0-2 according to Eastern Cooperative Oncology Group (ECOG), without significant cardiac, pulmonary, or hepatic dysfunction or active infection. All patients received a high-dose melphalan-containing preparative regimen supported with an infusion of previously collected and cryopreserved autologous peripheral blood stem cells [8]. Melphalan was administered over a 60-minute infusion on day -1 pre ASCT.…”
Section: Patientsmentioning
confidence: 99%
“…Patients with extremely reduced eGFR are frequently considered ineligible for autologous stem cell transplantation (ASCT) because of a higher risk of treatment-related toxicities, including death. However, in recent years, in several studies it was found that ASCT may be effective and safe in patients with severe renal impairment [4][5][6][7][8][9]. Moreover, in some studies it was found that severe renal impairment may be partly reversible in a proportion of patients, especially when ASCT is performed early in the course of the disease [10][11][12].…”
Section: Introductionmentioning
confidence: 99%